Mass culture of the rotifer Brachionus plicatilis under laboratory condition - Khathem, S. A.; Hassan, H. F.; Ghazi, A. H. (Iraqi Journal of Aquaculture, 2022)
In the present study the rotifer Brachionus plicatilis was cultured under controlled laboratory conditions, in Marine Science Center, Dept. of Marine Biology, the temperature was 22 ºC. The rotifers feeding on two type of food, the first was baker's yeast and second the animal manure. General, used the animal manure was better than baker's yeast. The density of rotifers culture at 22 ºC which fed on animal manure was 145 ind /ml, while growth rate was 2.67 and doubling time was 0.25 day. While, the density, growth rate and doubling time of rotifers culture at 22 ºC which fed on beakers yeast were 75 ind./ml, 2.01 and 0.34 day respectively. The importance of this study to determined the ability to depending on animal manure as cheap resource and available to improve rotifer growth compared with baker's yeast. Additional, to suitable period determined to culture of rotifer for supply it to larvae of fish and crustacean.